PEMBATASAN PENCANTUMAN KLAUSULA BAKU SEBAGAI UPAYA PERLINDUNGAN KONSUMEN DALAM PERJANJIAN SEWA BELI - Hendra Mahardika, I Gusti Ngurah Nyoman; Rai Setiabudhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Business actors give agreement with standard clauses that make the consumer does not have the bargaining power in the hire purchase agreement. The purpose of writing this article to know the responsibility of business operators to the security and limitation destroyed inclusion of standard clauses in a lease agreement as a legal protection for consumers. Writing is using this type of normative legal research, moving from the presence of vagueness norms / principles of law. Conclusion The results of this study are Law No. 8 of 1999 on Consumer Protection (BFL) does not prohibit businesses to make an agreement with the standard clause insofar as not inconsistent with the provisions of Article 18 paragraph (2) of Law No. 8 of 1999 on Consumer Protection (BFL).
Keywords: standard clause, the businessman, the protection of law